NAT10‐mediated mRNA N4‐acetylcytidine modification promotes bladder cancer progression. Issue 5 (6th May 2022) - Wang, Ganping; Zhang, Ming; Zhang, Yiming; Xie, Yanqi; Zou, Jiepeng; Zhong, Jianye; Zheng, Zhijia; Zhou, Xianghui; Zheng, Yuhang; Chen, Binshen; Liu, Chunxiao
Abstract: Background: Dysregulation of the epitranscriptome causes abnormal expression of oncogenes in the tumorigenic process. Previous studies have shown that NAT10 can regulate mRNA translation efficiency through RNA acetylation. However, the role of NAT10‐mediated acetylation modification in bladder cancer remains elusive. Methods: The clinical value of NAT10 was estimated according to NAT10 expression pattern based on TCGA data set and the tumor tissue array. Acetylated RNA immunoprecipitation sequencing was utilized to explore the role of NAT10 in mRNA ac4C modification. Translation efficiency and mRNA stability assay were applied to study the effect of NAT10‐deletion on target genes. The nude mouse model and genetically engineered mice were conducted to further verify the characteristics of NAT10 in promoting BLCA progression and regulating downstream targets. Results: NAT10 was essential for the proliferation, migration, invasion, survival and the stem‐cell‐like properties of bladder cancer cell lines. NAT10 was responsible for mRNA ac4C modification in BLCA cells, including BCL9L, SOX4 and AKT1. Deficient NAT10 in both xenograft and transgenic mouse models of bladder cancer reduced the tumor burden. Furthermore, acetylated RNA immunoprecipitation sequencing data and RNA immunoprecipitation qPCR results revealed that NAT10 is responsible for a set of ac4C mRNA modifications in bladder cancer cells. Inhibition of NAT10 led to a loss of ac4C peaks in these transcripts and represses the mRNA's stability and protein expression. Mechanistically, the ac4C reduction modification in specific regions of mRNAs resulting from NAT10 downregulation impaired the translation efficiency of BCL9L, SOX4 and AKT1 as well as the stability of BCL9L, SOX4. Conclusions: In summary, these findings provide new insights into the dynamic characteristics of mRNA's post‐transcriptional modification via NAT10‐dependent acetylation and predict a role for NAT10 as a therapeutic target in bladder cancer. Highlights: NAT10 is highly expressed in BLCA patients and its abnormal level predicts bladder cancer progression and low overall survival rate. NAT10 is necessary and sufficient for BLCA tumourigenic properties. NAT10 is responsible for ac4C modification of target transcripts, including BCL9L, SOX4 and AKT1. NAT10 may serve as an effective and novel therapeutic target for BLCA. Abstract : NAT10 is highly expressed in BLCA patients and its abnormal level predicts bladder cancer progression and low overall survival rate. NAT10 is necessary and sufficient for BLCA tumorigenic properties. NAT10 is responsible for ac4C modification of target transcripts, including BCL9L, SOX4 and AKT1. NAT10 may serve as an effective and novel therapeutic target for BLCA.